Longitudinal association of Apolipoprotein E polymorphism with lipid profile, type 2 diabetes and metabolic syndrome: Results from a 15 year follow-up study. (March 2022) - Pitchika, Anitha; Markus, Marcello Ricardo Paulista; Schipf, Sabine; Teumer, Alexander; Van der Auwera, Sandra; Nauck, Matthias; Dörr, Marcus; Felix, Stephan; Jörgen Grabe, Hans; Völzke, Henry; Ittermann, Till
Abstract: Aims: To examine the association of different APOE alleles with type 2 diabetes mellitus (T2DM) and metabolic syndrome (MetS) as well as the influence of high-sensitive C-reactive protein (hs-CRP) on these associations. Methods: We analyzed data from 3917 participants aged 20–81 years of the population-based Study of Health in Pomerania (SHIP) from Northeast Germany with a median follow-up time of 10.8 years. Linear and logistic mixed models were performed to test the association of APOE alleles with T2DM and MetS. Results: We observed 393 T2DM and 1411 MetS events at baseline, and 576 T2DM and 1342 MetS events over the follow-up. The E4 carriers had a lower odds of developing T2DM (OR: 0.47 [0.24, 0.94]) than E3 homozygotes even after adjustment for potential confounders. The E2 carriers showed no associations. The inverse association between E4 alleles and T2DM moderately attenuated after adjustment for hs-CRP levels. The lower odds of developing T2DM in E4 carriers was more pronounced in participants without obesity, hypertension or MetS. However, both E2 and E4 carriers had higher odds of developing MetS (E2 OR: 1.45 [1.03, 2.03]; E4 OR: 1.56 [1.17, 2.09]) than E3 homozygotes. Conclusions: While the presence of APOE E4 allele might increase the chance of MetS through its major action on lipids, E4 allele might offer a protection towards T2DM through its influence on inflammation.